The Role of Pertamina Patra Niaga Integrated Terminal Banjarmasin in Realizing Sustainable Development Goals in Indonesia Through Environmental Social Responsibility Programs - Adi Lukman Arifin*; Fikri Jati Wibowo; Dody P. Sihotang; Haryono Haryono; Amrizarois Ismail (Riwayat: Educational Journal of History and Humanities, 2023)
Empowerment of local communities is an important aspect that must be carried out by all parties as a form of caring for fellow human beings. The sense of concern for the surrounding community is also driven by the Pertamina Integrated Terminal Banjarmasin by creating a program that targets several fields including the economic, environmental, education and health sectors. With that explained that research is a type of qualitative research with data sources derived from library sources. There are three important questions in this research. First, what is the role of Pertamina Patra Niaga Integrated Terminal Banjarmasin in realizing the Sustainable Development Goals in Indonesia? Second, how is the Pertamina Patra Niaga Integrated Terminal Banjarmasin realized in realizing the economic and social development of the Banjarmasin community? Third, what is the urgency of the Pertamina Patra Niaga Integrated Terminal Banjarmasin Corporate Social Responsibility (CSR) program for the community? The theme taken in this study is community empowerment around the company through Corporate Social Responsibility (CSR). The results of this study show evidence that Pertamina Patra Niaga Integrated Terminal Banjarmasin is capable of empowering the surrounding community by providing teaching in the fields of economics, environment, education and health. The success of the program initiated by Pertamina Patra Niaga Integrated Terminal Banjarmasin also comes from the social factor of Human Resources (HR) in the region having an interest in developing and learning. With human resources who have been equipped with an understanding related to ecology, natural resources in the Banjarmasin environment can be developed.